The Experimental Investigation On Performance Of Cotton Seed Biodiesel With Nano Additive In Single Cylinder Diesel Engine - Megersa, Lemma (ASTU, 2018)
Biodiesel made from the vegetable oils found to check one among the most process alternatives to petro diesel in solving the issues like depletion of petroleum sources, environmental pollution etc. For a country like Ethiopia with large trade gas-producing home grownup with ecofriendly fuel is an urgent necessity. For Ethiopia with wide cultivation of cotton seed oil would be a really smart inedible feedstock for preparation of biodiesel. Far more work is reviewed to understand biodiesel behavior under varied designs of engines, before its commercialisation. Biodiesel has several drawbacks like higher viscosity, low calorific value, cold flow issues, higher emission, shorter storage life etc. In recent days with the development of nanotechnology, addition of nano particles for improving the performance of fuels attracting the attention of researchers. Thus during this work it's aimed to test the performance of cotton seed oil biodiesel with cerium oxide (CeO2) nano particles as additive. This work goes through the varied stages like production of biodiesel, admixture of nano particles within the biodiesel-diesel blends in different proportion using ultrasonicator. The other was, testing the effect of nano additives on physichemical propertis of the fuel blend, testing the stability of fuel blend with nano particles, testing the performance and testing exhaust emission in diesel engine. The blend were ready as B10 (90% diesel and 10% biodiesel in volume), B20 (80% diesel and 20% biodiesel in volume), B20+50ppm (80% diesel and 20% biodiesel and 0.05 gm/l cerium oxide) in volume, B20 + 100ppm (80% diesel and 20% biodiesel and 0.1 mg/l cerium oxide) in volume, B25 (75% diesel and 25% biodiesel) in volume. From the performance test results, the cotton seed oil fuel blended with cerium oxide shows 4.5kW, 4.68kW, 18.43Nm and 18.52Nm with increasing point of brake power, brake torque. Also from characteristic‘s test, its viscosity was 3.67cSt for biodiesel. Addition of CeO2 improves exhaust emission compared to pure diesel (B0). The brake specific fuel consumption of cotton seed fuel blended with cerium was decreased compared to the diesel. Generally, it may be concluded from the experimental investigations that the cotton seed oil fuel blended with cerium oxide nanoparticle can become an alternative source of fuel and Optimum blend fuel will be found for replacement of petro diesel in the future.

Biodiesel Made From The Vegetable Oils Found To Check One Among The Most Process Alternatives To Petro Diesel In Solving The Issues Like Depletion Of Petroleum Sources, Environmental Pollution Etc. For A Country Like Ethiopia With Large Trade Gas-Producing Home Grownup With Ecofriendly Fuel Is An Urgent Necessity. For Ethiopia With Wide Cultivation Of Cotton Seed Oil Would Be A Really Smart Inedible Feedstock For Preparation Of Biodiesel. Far More Work Is Reviewed To Understand Biodiesel Behavior Under Varied Designs Of Engines, Before Its Commercialisation. Biodiesel Has Several Drawbacks Like Higher Viscosity, Low Calorific Value, Cold Flow Issues, Higher Emission, Shorter Storage Life Etc. In Recent Days With The Development Of Nanotechnology, Addition Of Nano Particles For Improving The Performance Of Fuels Attracting The Attention Of Researchers. Thus During This Work It's Aimed To Test The Performance Of Cotton Seed Oil Biodiesel With Cerium Oxide (Ceo2) Nano Particles As Additive. This Work Goes Through The Varied Stages Like Production Of Biodiesel, Admixture Of Nano Particles Within The Biodiesel-Diesel Blends In Different Proportion Using Ultrasonicator. The Other Was, Testing The Effect Of Nano Additives On Physichemical Propertis Of The Fuel Blend, Testing The Stability Of Fuel Blend With Nano Particles, Testing The Performance And Testing Exhaust Emission In Diesel Engine. The Blend Were Ready As B10 (90% Diesel And 10% Biodiesel In Volume), B20 (80% Diesel And 20% Biodiesel In Volume), B20+50ppm (80% Diesel And 20% Biodiesel And 0.05 Gm/L Cerium Oxide) In Volume, B20 + 100ppm (80% Diesel And 20% Biodiesel And 0.1 Mg/L Cerium Oxide) In Volume, B25 (75% Diesel And 25% Biodiesel) In Volume. From The Performance Test Results, The Cotton Seed Oil Fuel Blended With Cerium Oxide Shows 4.5kw, 4.68kw, 18.43nm And 18.52nm With Increasing Point Of Brake Power, Brake Torque. Also From Characteristic??S Test, Its Viscosity Was 3.67cst For Biodiesel. Addition Of Ceo2 Improves Exhaust Emission Compared To Pure Diesel (B0). The Brake Specific Fuel Consumption Of Cotton Seed Fuel Blended With Cerium Was Decreased Compared To The Diesel. Generally, It May Be Concluded From The Experimental Investigations That The Cotton Seed Oil Fuel Blended With Cerium Oxide Nanoparticle Can Become An Alternative Source Of Fuel And Optimum Blend Fuel Will Be Found For Replacement Of Petro Diesel In The Future.
The Experimental Investigation On Performance Of Cotton Seed Biodiesel With Nano Additive In Single Cylinder Diesel Engine